NATO AND EU MARITIME MILITARY POLICY: NATO AND EU MARITIME MILITARY POLICY - Antonova, Mariela; Karatash, Emine (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This article examines the strategic directions, institutional mechanisms and operational initiatives of the maritime military policy of NATO and the European Union (EU). It analyses the role of the two alliances in ensuring maritime security, protecting trade routes and countering new threats such as piracy, illegal migration and hybrid operations. It presents a comparative study of the concepts, naval capabilities and joint missions of NATO and the EU in the maritime environment.